Impact of Covid-19 on the global orthopaedic research output - Wolf, Milan; Landgraeber, Stefan; Maass, Wolfgang; Orth, Patrick (Frontiers in Surgery, 2022)
The pandemic led to a significant change in the clinical routine of many orthopaedic surgeons. To observe the impact of the pandemic on scientific output all studies published in the fields of orthopaedics listed in the Web of Science databases were analysed regarding the scientific merit of the years 2019, 2020, and 2021. Subsequently, correlation analyses were performed with parameters of regional pandemic situation (obtained from WHO) and economic strength (obtained from the World Bank). The investigations revealed that the Covid-19 pandemic led to a decrease in the annual publication rate for the first time in 20 years (2020 to 2021: -5.69%). There were regional differences in the publication rate, which correlated significantly with the respective Covid-19 case count (r=-.77, p<0.01), associated death count (r=-.63, p<0.01), and the gross domestic product per capita (r=-.40, p<0.01) but not with the number of vaccinations (r=.09, p=0.30). Furthermore, there was a drastic decrease in funding from private agencies (relative share: 2019: 36.43%, 2020: 22.66%, 2021: 19.22%), and a balanced decrease in publication output for research areas of acute and elective patient care. The Covid-19 pandemic resulted in a decline in orthopaedic annual publication rates for the first time in 20 years. This reduction was subject to marked regional differences and correlated directly with the pandemic load and was associated with decreased research funding from the private sector.